2000
DOI: 10.1207/s15516709cog2403_2
|View full text |Cite
|
Sign up to set email alerts
|

Categorical Perception and Conceptual Judgments by Nonhuman Primates: The Paleological Monkey and the Analogical Ape

Abstract: Studies of the conceptual abilities of nonhuman primates demonstrate the substantial range of these abilities as well as their limitations. Such abilities range from categorization on the basis of shared physical attributes, associative relations and functions to abstract concepts as reflected in analogical reasoning about relations between relations. The pattern of results from these studies point to a fundamental distinction between monkeys and apes in both their implicit and explicit conceptual capacities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
2
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(176 citation statements)
references
References 99 publications
(71 reference statements)
6
166
2
1
Order By: Relevance
“…As described in the Introduction, success in these tasks is possible only when the subject attends to the relation between items (e.g., whether two items are the same or different). The subject must transfer the learned relations between familiar items to novel ones during testing (30)(31)(32)(33), comparable to the requirements for success in our artificial grammar learning task. The ability to perform such a relational match-to-sample task long was thought to be unique for humans; it also has been demonstrated in some great ape species (30) and recently has been demonstrated in crows and amazon parrots (32, 33, but also see ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described in the Introduction, success in these tasks is possible only when the subject attends to the relation between items (e.g., whether two items are the same or different). The subject must transfer the learned relations between familiar items to novel ones during testing (30)(31)(32)(33), comparable to the requirements for success in our artificial grammar learning task. The ability to perform such a relational match-to-sample task long was thought to be unique for humans; it also has been demonstrated in some great ape species (30) and recently has been demonstrated in crows and amazon parrots (32, 33, but also see ref.…”
Section: Discussionmentioning
confidence: 99%
“…Next they are tested with pairs of novel items that do not share a physical resemblance with the training stimuli, but do share the same underlying structure, such as CC or CD. Such a task thus requires the matching of relations between relations (29)(30)(31)(32)(33). Similarly, learning to identify correct sequences of novel auditory items, such as an XYX or XXY structure, requires that the animal first detects that the relation between the X and Y items differs in the XYX and XXY samples and next abstracts this relation to novel samples.…”
mentioning
confidence: 99%
“…Thompson and his colleagues Thompson & Oden, 2000) suggested that the results from symbol-sophisticated and symbol-naïve chimpanzees sup-port the hypothesis that prior experience with symbols for relations per se is sufficient for chimpanzees to immediately match higher-order analogical relations between relations (cf., Premack, 1988;Smith, King, Witt, & Rickel, 1975). Providing concrete tokens to represent abstract same/different relations perhaps permits the covert recoding of the abstract (i.e., propositional) relations as imaginal representations of the tokens, thereby reducing the analogical matching task to one that is functionally equivalent to a physical same/different matching task.…”
Section: Categorical Relational Matching By Nonhuman Primates and Chimentioning
confidence: 99%
“…One possibility is that choice of the O and p cues was a function of the matching or nonmatching outcome of a computational operation performed on individual withinpair items rather than on the perception of relational identity or nonidentity (Thompson & Oden, 2000;Thompson, Oden, & Washburn, in preparation). Application of matching and nonmatching operators is likely to occur in all nonhuman primates, as well as in mammals and birds (cf., Thompson, 1995;Thompson & Oden, 2000).…”
Section: Do Labels Affect Categorical Analogical Equivalence Judgmentmentioning
confidence: 99%
See 1 more Smart Citation